Relationship of platelet indices with acute stent thrombosis in patients with acute coronary syndrome - Balli, Mehmet; Taşolar, Hakan; Çetin, Mustafa; Cagliyan, Caglar Emre; Gözükara, Mehmet Yavuz; Yilmaz, Mahmut; Elbasan, Zafer; Cayli, Murat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Despite major advances in stent technology and antithrombotic therapy, the development of stent thrombosis continues to be a major problem in patients who have undergone percutaneous coronary intervention (PCI). Although a few studies have investigated the relationship between early stent thrombosis and platelet activity, the relationship between acute stent thrombosis (AST) (within the first 24 h) and platelet indices is unclear. Aim: We investigated the relationship between AST development and platelet indices in acute coronary syndrome patients. Material and methods: In our case-control study, 33 patients who underwent PCI with subsequent AST development and 59 patients without AST were selected by propensity analysis. We compared the clinical, angiographic, and laboratory data between the AST and control groups. Results : Mean platelet volume (MPV) (p = 0.002) and platelet distribution width (p = 0.014) were significantly higher and platelet count (p = 0.017) was significantly lower in the AST group. Logistic regression analyses showed that MPV was a significant independent predictor of AST (OR = 1.67; 95% CI: 1.11–2.51; p = 0.013). In the ROC analyses, the cut-off value of MPV to detect AST was > 9.1 fl with a sensitivity of 90.9%, a specificity of 42.4%, a positive predictive value of 46.9% and a negative predictive value of 89.3% (AUC: 0.687, 95% CI: 0.582–0.780, p = 0.001). Conclusions : Our study shows that baseline MPV predicts the development of AST in patients with ACS. Mean platelet volume therefore might be an easily accessible marker in the identification of patients at high risk for the development of AST.